Clinicopathological features and prognosis of IgA vasculitis nephritis with nephrotic-range proteinuria in children. - Xi, Leying; Sun, Yuying; Chen, Yawei; Yang, Xiaoqing; Su, Hang; Ren, Xianqing (Pediatric Nephrology, 2024)
Background: To investigate the clinical features, kidney pathology, treatment regimens, and clinical outcomes of IgA vasculitis nephritis (IgAVN) with nephrotic-range proteinuria in children. Methods: A retrospective review of children diagnosed with IgAVN between January 2019 and December 2022 was conducted. Participants were divided into two groups based on their urine protein/creatinine (UPCR) levels. Biodata, clinical characteristics, laboratory findings, pathologic features, treatment regimens, and outcomes were abstracted from case records and analyzed. Results: A total of 255 children were identified, 94 with nephrotic-range proteinuria (UPCR ≥ 200 mg/mmol) and 161 with non-nephrotic proteinuria (UPCR < 200 mg/mmol). Patients in the nephrotic-range proteinuria group were significantly younger and had worse grades of glomerular and acute tubulointerstitial injury compared to those in the non-nephrotic proteinuria group. Higher levels of blood urea nitrogen (BUN), D-dimer (DD), and fibrin degradation products (FDP), and lower levels of total protein (TP), albumin (ALB), urine creatinine (Cr), prothrombin time (PT), activated partial thromboplastin time (APTT), IgG, CD3 + cells, and CD4 + cells were found in patients in the nephrotic-range proteinuria group. Clinical outcome of patients with nephrotic-range proteinuria was significantly associated with ISKDC grading, proportion of glomerular crescents and severity of acute tubulointerstitial injury. Conclusions: Children with nephrotic-range proteinuria exhibit more severe disordered immunologic function, hypercoagulability, glomerular and tubulointerstitial pathological damage, and have worse outcomes than those with lower proteinuria levels. Clinicians should pay great attention to the kidney injury and more extensive studies are required to identify optimal treatment regimens to improve outcomes in patients.